Analysis of Attitude, Subjective Norm And Perceived Behavioral Control on The Consumer’s Purchasing Behavior Toward Halal Skincare Product in Indonesian Women - Wahyu Retno Dumillah (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This study discusses about attitude, subjective norm and perceived behavioral control on the consumer’s purchasing behavior toward halal skincare product in Indonesian women. Design/methodology/approach: The data obtained were processed using Structural Equation Modeling (SEM) method with SmartPLS3. Findings: The results showed that attitude had a positive and significant influence on buying halal skincare products. Research limitations/implications: Datas were collected through questionnaires that distributed online. The number of respondents who involved were 54 respondents. Practical implications: This study also shows that intention has a positive and significant influence on purchasing behavior of halal skincare products Originality/value: This study calculates and finds the truth about attitudes, subjective norms and perceived behavioral control on consumer buying behavior towards halal skin care products in Indonesian women using a questionnaire. Paper type: Research Paper